Implementasi Undang-undang Pornografi terhadap Penyanyi Dangdut dalam Prespektif Hukum Islam - Amin, Achmad Agus (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
Dangdut music is one type of music genre found in Indonesia. It is the most loved music by the majority public. However, dangdut music is often misrepresented lately by individuals as the source of pornography. This paper aims to find out how the implementation of prescriptions and constraints of pornography on dangdut singers in the view of the Pornography Law, and Fiqh Siyâsah ideas. The study determined that the prohibitions and restrictions on pornography contained in Law Number 44 of the Year 2008 have not been fully implemented. The Law is applicable only if certain events occur and dangdut singers have violated the restrictions. So it is clear that there is a lacuna between the prevailing rules and the existing phenomena. In terms of Islamic law, the pornographic acts committed by dangdut singers are considered as prohibitory deeds and against Islamic law. It comes under ta'z?r punishment.